Empowering disaster volunteers through a web-based information system for health workforce and logistics coordination - Emmelia Kristina Hutagaol; Afif Wahyudi Hidayat; Nico Suwarno; Nurali Nurali; Joao Manuel Correia Ximenes (International Journal of Public Health Science (IJPHS), 2026)
Digital transformation plays a critical role in strengthening disaster management systems, particularly in disaster-prone countries such as Indonesia. Despite the availability of several government-led digital platforms, limited systems integrate volunteer coordination, health workforce mapping, and logistics tracking within a unified framework. This study aimed to develop and evaluate a web-based information system designed to empower disaster volunteers by integrating volunteer profiling, healthcare human resource availability, logistics documentation, and public education features. A mixed-methods descriptive analytical design was employed. Qualitative data were collected through in-depth interviews to identify system requirements and operational challenges, while quantitative data were obtained from structured questionnaires completed by 71 of 75 health-background from TAGANA Rajawali Indonesia Foundation members and at least one disaster respon experience. Descriptive non-parametric analysis informed system design and feature prioritization. Results showed that 100% of respondents supported the development of a digital coordination platform, 94.7% preferred WhatsApp integration for communication, and 86.7% were willing to contribute as digital resource persons for public education. The developed system integrates real-time manpower mapping, logistics tracking, donation management, multimedia documentation, and reporting dashboards. This model addresses a critical gap in volunteer-centered digital disaster management and strengthens community-based preparedness by improving coordination efficiency, transparency, and public health resilience.